Load Control for Locking: The 'Half-and-Half' approach - Carey, Michael J; Krishnamurthi, Sanjay; Livny, Miron (University of Wisconsin-Madison Department of Computer Sciences, 1989)
A number of concurrency control performance studies have shown that, under high levels of data contention, concurrency control algorithms can exhibit thrashing behavior which is detrimental to overall system performance. In this paper, we present an approach to eliminating thrashing in the case of two-phase locking, a widely used concurrency control algorithm. Our solution, which we call the ?Half-and-Half? Algorithm, involves monitoring the state of the DBMS in order to dynamically control the multiprogramming level of the system. Results from a performance study indicate that the Half-and-Half algorithm can be very effective at preventing thrashing under a wide range of operating conditions and workloads.